2023
DOI: 10.3390/ijms241914914
|View full text |Cite
|
Sign up to set email alerts
|

Platelets as Potential Non-Traditional Cardiovascular Risk Factor—Analysis Performed in Healthy Donors

Patrycja Szymańska,
Bogusława Luzak,
Przemysław Siarkiewicz
et al.

Abstract: Abnormal lipid profile, increased glucose level, and elevated body weight are traditional cardiometabolic risk factors; however, the role of platelets in the development of cardiovascular disease (CVD) is increasingly being highlighted. The aim of this study was to select platelet-related parameters (non-genetic molecular and routine laboratory measurements) that may be associated with increased cardiovascular risk among healthy populations. We evaluated the level of platelet indices, platelet-based inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…18,34 To date, some studies have underscored the prognostic value of PHR in various clinical contexts. 17,34,35 For instance, noteworthy findings from Jialal et al found that elevated PHR values in patients progressing towards metabolic syndrome significantly correlated with all cardio-metabolic features, suggesting its potential as both a marker for metabolic syndrome and a promising predictor of cardiovascular risk and thrombotic incidents. 18 Furthermore, Szymańska et al observed significantly higher PHR levels in subgroups with elevated blood glucose (P =0.041) and increased body mass index (P =0.001), highlighting its potential in stratifying patients based on glucose and body mass index.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18,34 To date, some studies have underscored the prognostic value of PHR in various clinical contexts. 17,34,35 For instance, noteworthy findings from Jialal et al found that elevated PHR values in patients progressing towards metabolic syndrome significantly correlated with all cardio-metabolic features, suggesting its potential as both a marker for metabolic syndrome and a promising predictor of cardiovascular risk and thrombotic incidents. 18 Furthermore, Szymańska et al observed significantly higher PHR levels in subgroups with elevated blood glucose (P =0.041) and increased body mass index (P =0.001), highlighting its potential in stratifying patients based on glucose and body mass index.…”
mentioning
confidence: 99%
“…18 Furthermore, Szymańska et al observed significantly higher PHR levels in subgroups with elevated blood glucose (P =0.041) and increased body mass index (P =0.001), highlighting its potential in stratifying patients based on glucose and body mass index. 35 In addition to its correlation with metabolic syndrome and cardiovascular risk, prior investigations have shown that elevated PHR levels are associated with stenosis in multiple coronary arteries, correlating with CAD severity measured by Gensini score. 34 Moreover, substantial evidence has established the well-acknowledged pathological mechanism of chronic inflammation underlying both T2DM and cardiovascular disease (CVD).…”
mentioning
confidence: 99%